Review on Effect of the Chemical Composition of some Pharmaceutical Vaccines and their Biochemical Efficacy with Chemical Techniques - Nagham Mahmood Aljamali; Sabreen Farhan Jawad (International Journal of Photochemistry and Photochemical Research, 2026)
Chemical compounds are fundamental components in the formulation of medicines and vaccines, playing a critical role in ensuring their safety, stability, and effectiveness. Vaccines contain a combination of active and inactive ingredients, including weakened or inactivated viruses or bacteria, toxins, preservatives, stabilizers, adjuvants, antibiotics, and minerals. The active ingredient is an antigen, which stimulates the body's immune system to recognize and defend against specific infectious diseases. Adjuvants, such as aluminum salts, are commonly added to enhance the immune response and improve antibody production. Other components, including gelatin and antibiotics, help maintain vaccine stability and prevent microbial contamination during manufacturing and storage. The chemical composition of vaccines is carefully evaluated using a range of analytical techniques to ensure quality, purity, and consistency. Among these, molecular spectroscopy is widely used to identify and quantify small-molecule components, preservatives, adjuvants, and trace impurities. This technique provides detailed molecular information, making it indispensable for the characterization and quality control of complex vaccine formulations. Vaccines are broadly classified into live attenuated and inactivated vaccines. Live attenuated vaccines contain weakened forms of viruses or bacteria that retain their ability to stimulate a strong and long-lasting immune response without causing disease in healthy individuals. In contrast, inactivated vaccines contain killed pathogens or their components and generally require booster doses to maintain immunity. Although live attenuated vaccines are highly effective, they may not be suitable for individuals with weakened immune systems. Overall, understanding the chemical composition and analytical evaluation of vaccines is essential for ensuring their efficacy, safety, and successful prevention of infectious diseases.
Keywords: Analytical Techniques; adjuvants; chemical composition; inactivated vaccines; live attenuated vaccines; molecular spectroscopy; vaccines